Stigma associated with parental depression or cancer: Impact on spouse and offspring's cortisol levels and socioemotional functioning. (December 2020) - Lupien, Sonia J.; Roy, Denis-Claude; Raymond, Catherine; Leclaire, Sarah; Wan, Nathalie; Labelle, Réal; Giguère, Charles-Édouard; Ouellet-Morin, Isabelle
Abstract: Stress associated with caring for a mentally ill spouse can adversely affect the health status of caregivers and their children. Adding to the stress of caregiving is the stigma often placed against spouses and children of people with mental illness. Contrary to mental illness, many physical disorders such as cancer may be less stigmatized (expect pulmonary cancer). In this study, we measured externalized and internalized stigma, as well as psychological (depressive symptoms and stressful life events) and physiological (basal salivary cortisol levels) markers of stress in 115 spouses and 154 children of parents suffering from major depressive disorder, cancer, or no illness (control group). The results show that spouses and children from families with parental depression present significantly more externalized stigma than spouses and children from families with parental cancer or no illness, although we find no group differences on internalized stigma. The analysis did not show a significant group difference either for spouses or their children on depressive symptomatology, although spouses from the parental depression group reported greater work/family stress. Finally, we found that although for both spouses children the awakening cortisol response was greater on weekdays than on weekend days, salivary cortisol levels did not differ between groups. Bayes factor calculated on the null result for cortisol levels was greater than 100, providing strong evidence for the null hypothesis H0 . Altogether, these results suggest an impact of stigma toward mental health disorder on psychological markers of stress but no impact of stigma on physiological markers of stress. We suggest that these results may be due to the characteristics of the families who participated in the present study.